The Living Conditions Diamond: An Analytical and Theoretical Framework for Understanding Slums - Gulyani, Sumila (2012)
What constitutes a 'slum' is much debated in the urban poverty and affordable housing literature. We argue that a focus on living conditions can help clarify this and present a framework, the living conditions diamond, for detailing living conditions and determining how the settlements we deem 'slums' compare with each other and with nonslum settlements. The diamond distills living conditions into four dimensions: (i) tenure, (ii) infrastructure, (iii) unit quality, and (iv) neighbourhood and location. This framework depicts conditions in graphic terms enabling comparison of conditions within and across cities. The diamond moves us beyond the notion that slums are homogeneously poor in quality, and facilitates analyses that can reveal why they differ. Settlements in Nairobi, Kenya and Dakar, Senegal are compared.